The most common diagnoses of care and nursing activities in children with congenital heart defects - Veselinović Đurđina (Association of Nurses Technicians and Midwives, 2023)
Congenital heart defects are the most common chronic congenital anomalies in childhood. They occur as a consequence of the action of genetic and multifactorial factors. Feasibility is present in both sexes, regardless of the economic situation of the country. They lead to structural and functional changes in the heart muscle, thus interfering with its normal functioning. The most effective method of treating and solving the problem of heart defects is surgery. By being exposed to an invasive procedure, they encounter numerous postoperative risks, and it is necessary to provide maximum care and support. The formation of a care team, the application of the health care process, ensures adequate conditions during the stay in the tertiary level health institution. This paper presents all the necessary segments of nursing care, in children with a diagnosis of congenital heart defect. The segments arise from the process of health care. Professional action is based on independent and interdependent nursing interventions. Key words: congenital heart defect, cardiac intensive care, nursing diagnoses of heart defects in children, postoperative care of heart defects.